LAMB3 Mutations Causing Autosomal-dominant Amelogenesis Imperfecta - Kim, J.W. (SAGE Publications, 2013)
Amelogenesis imperfecta (AI) can be either isolated or part of a larger syndrome. Junctional epidermolysis bullosa (JEB) is a collection of autosomal-recessive disorders featuring AI associated with skin fragility and other symptoms. JEB is a recessive syndrome usually caused by mutations in both alleles of COL17A1, LAMA3, LAMB3, or LAMC2. In rare cases, heterozygous carriers in JEB kindreds display enamel malformations in the absence of skin fragility (isolated AI). We recruited two kindreds with autosomal-dominant amelogenesis imperfecta (ADAI) characterized by generalized severe enamel hypoplasia with deep linear grooves and pits. Whole-exome sequencing of both probands identified novel heterozygous mutations in the last exon of LAMB3 that likely truncated the protein. The mutations perfectly segregated with the enamel defects in both families. In Family 1, an 8-bp deletion (c.3446_3453del GACTGGAG) shifted the reading frame (p.Gly 1149Glufs*8). In Family 2, a single nucleotide substitution (c.C3431A) generated an in-frame translation termination codon (p.Ser1144*). We conclude that enamel formation is particularly sensitive to defects in hemidesmosome/basement-membrane complexes and that syndromic and non-syndromic forms of AI can be etiologically related.